Max's Christmas - Wells, Rosemary (New York : Dial Books for Young Readers, 1986)
Despite his sister Ruby's admonitions, Max waits up on Christmas Eve to see Santa Claus coming down the chimney.
Children's Catalog (Wilson)
ALA Notable Books
*SLJ*
1.5
K-3
Keywords: Santa Claus -- Fiction; Santa Claus -- Fiction; Christmas -- Fiction; Brothers and sisters -- Fiction; Rabbits -- Fiction; Christmas -- Fiction; Rabbits -- Fiction